2022
DOI: 10.17309/tmfv.2022.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Attitudes towards Inclusion of Visually Impaired Students in Physical Education Classes: Gender Differences

Abstract: Study purpose. The study purpose was to investigate gender differences in children’s attitudes toward the inclusion of a student with visual impairment in physical education classes. Materials and methods. The study sample comprised 419 able-bodied primary school students in 6th to 9th grade (boys, n=204, mean age 13.23±1.17 years; girls, n=215, mean age 13.08±1.19 years). A modified version of the standardized attitudinal questionnaire CAIPE-R for the inclusion of visually impaired (VI) students was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Following the implementation of inclusive physical activity sessions, in our research, students demonstrated a significant improvement in their perception of learning related to disability. These findings endorse the notion that inclusive education, especially inclusive physical activity, can effectively changing attitudes and perceptions towards disability have an impact on other variables, as noted in studies such as that of Nemček (2022). Additionally, the outcomes emphasize the fundamental role of educators in endorsing and executing all-inclusive knowledge.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Following the implementation of inclusive physical activity sessions, in our research, students demonstrated a significant improvement in their perception of learning related to disability. These findings endorse the notion that inclusive education, especially inclusive physical activity, can effectively changing attitudes and perceptions towards disability have an impact on other variables, as noted in studies such as that of Nemček (2022). Additionally, the outcomes emphasize the fundamental role of educators in endorsing and executing all-inclusive knowledge.…”
Section: Discussionsupporting
confidence: 75%
“…There is a growing number of initiatives, including lectures, seminars and workshops, aimed at developing inclusive perspectives for future teachers, involving people with and without disabilities (Campos et al, 2021). Exposure to first-hand experiences fosters positive attitudes towards disability, which are later applied in the teaching profession (Abellán et al, 2018;Kwatubana & Bosch, 2019, Nemček, 2022. In this way, a continuous cycle of improving general perceptions of disability is created (Duk et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, there are respondents who say that Goals 5 and 10 are not related to physical culture and sport. However, the issues of social equality and gender have been facing society for decades and are very relevant and discussed in the field of physical culture and sports (Kempe-Bergman et al, 2020;Eime et al, 2021;Nemček, 2022). Paralympic sport is also gaining ground and is a way to reduce social inequality (Foster et al, 2019;Goh, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The description of the students with disorders was followed by statements that were summarized in two parts; (1) statements related to social interactions between students with disorders and ablebodied students in inclusive PE and (2) statements related to modifications of sports game rules for students with disorders. The social interactions domain contained 5 statements, such as If Silvia was with me in PE, I would have fun with her, and I would be her friend; and the rule modification domain also contained 5 statements, such as It would be good if nobody could take the ball away from Boris after the pass (Nemček, 2022(Nemček, , 2024. The attitudes, reflected in the degree of agreement with the statements, were rated by able-bodied church school students on a 4-point Likert scale as follows: score 1 -disagree, score 2 -rather disagree, score 3 -rather agree, score 4 -agree.…”
Section: Methodsmentioning
confidence: 99%